2014
DOI: 10.1155/2014/571682
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Immobilization ofβ-Galactosidase ontoκ-Carrageenan Gel Beads Using Response Surface Methodology and Its Applications

Abstract: β-Galactosidase (β-gal) was immobilized by covalent binding on novel κ-carrageenan gel beads activated by two-step method; the gel beads were soaked in polyethyleneimine followed by glutaraldehyde. 22 full-factorial central composite experiment designs were employed to optimize the conditions for the maximum enzyme loading efficiency. 11.443 U of enzyme/g gel beads was achieved by soaking 40 units of enzyme with the gel beads for eight hours. Immobilization process increased the pH from 4.5 to 5.5 and operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…The observed R 2 was in reasonable agreement with the adjusted R 2 of 0.887. This result confirmed a satisfactory adjustment of the quadratic model of the experimental data [19]. All the previous results reflected the applicability and accuracy of the central composite design for optimization of levansucrase immobilization process.…”
Section: Physiochemical Analysis Of Levansupporting
confidence: 82%
See 3 more Smart Citations
“…The observed R 2 was in reasonable agreement with the adjusted R 2 of 0.887. This result confirmed a satisfactory adjustment of the quadratic model of the experimental data [19]. All the previous results reflected the applicability and accuracy of the central composite design for optimization of levansucrase immobilization process.…”
Section: Physiochemical Analysis Of Levansupporting
confidence: 82%
“…The K m value for free and immobilized levansucrase was 2.5 and 2.85 mg/ ml, respectively. An increase in K m after enzyme immobilization could be back to the low substrate diffusion rate to the enzyme active site [19]. The increase in K m value after immobilization was mentioned by many other investigators [30].…”
Section: Effect Of Substrate Concentration On the Activity Of Free Anmentioning
confidence: 82%
See 2 more Smart Citations
“…Km value for immobilized enzyme increased from 22.9 mM (for free enzyme) to 61.6mM while _max value was decreased from 177.1 _mol/min (for free enzyme) to 131.2mol/min. The full conversion experiment showed that the developed IβGS was active as compared to the free enzyme, and achieved 100% lactose hydrolysis after 4h of cycle operation 29 .…”
Section: Immobilization Of βG On Polymeric/mesoporous Matrices Via Glmentioning
confidence: 99%